2022
DOI: 10.3390/nu14194130
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Thyroid: An Interesting Alliance

Abstract: The Mediterranean diet, recognized as being cultural heritage by UNESCO, is mostly plant-based and includes a high consumption of whole-grain, fruit, and vegetables with a moderate consumption of alcohol during meals. Thus, it provides a small amount of saturated fatty acids and a high quantity of antioxidants and fiber. For this reason, it has been considered to have an important role in preventing cardiovascular diseases, chronic kidney diseases, type 2 diabetes mellitus, and cancer, but its relationship wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 119 publications
1
8
0
Order By: Relevance
“…Late-night snacking habits are also considered to be one of the risk factors affecting thyroid function. Studies have shown that regular and reasonably arranged intake of meat, staple foods, vegetables, and fruits are beneficial for preventing thyroid function disorders ( 40 ), which is consistent with the findings of this paper. A Mediterranean characteristic diet, low in animal foods and high in plant foods, is more protective for thyroid function than a high animal foods diet ( 41 ) and may be related to the balanced gain in nutrient intake from a good diet.…”
Section: Discussionsupporting
confidence: 92%
“…Late-night snacking habits are also considered to be one of the risk factors affecting thyroid function. Studies have shown that regular and reasonably arranged intake of meat, staple foods, vegetables, and fruits are beneficial for preventing thyroid function disorders ( 40 ), which is consistent with the findings of this paper. A Mediterranean characteristic diet, low in animal foods and high in plant foods, is more protective for thyroid function than a high animal foods diet ( 41 ) and may be related to the balanced gain in nutrient intake from a good diet.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, the nutritional needs of patients suffering from HT have been discussed in the literature, with still inconclusive and sometimes conflicting results [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. On the other hand, a protective or predisposing role of specific dietary traits has been investigated to propose a healthy diet model [ 12 , 61 , 62 , 63 , 64 , 65 ]. Indeed, current options for preventive interventions in subjects at risk of developing AITD are still very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the intriguing link between nutrition and health issues in the setting of AIDs, including rheumatoid arthritis, multiple sclerosis, psoriasis, intestinal bowel diseases, and HT, consistently indicating MD traits as protective against autoimmunity, as opposed to the WTD [ 65 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to underscore the significant impact of dietary on thyroid hormone levels. As an example, the Mediterranean Diet seems to have a beneficial effect on preventing thyroid diseases, including cancer [ 86 , 87 ]. Specifically, the synthesis of thyroid hormones depends on iodine.…”
Section: Hypothyroidism and Dietmentioning
confidence: 99%